PENGARUH KONSENTRASI ZPT AUKSIN DAN PANJANG ENTRES TERHADAP PERTUMBUHAN BIBIT TANAMAN ALPUKAT (Persea americana L.) - Eka Adi Supriyanto; Wadi Yulianto (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
Avocado is a crops that grows in tropical and sub-tropical. This research has a purpose that want to knows about what is the effect if avocado is concentration of auxin growth regulator and entres length on growth of avocado plant seeds, and interaction. This research was did in Pododadi village, Wonorejo hamlet Karanganyar district, Pekalongan county, this research uses randomized block designthat has 2 factors with 3 time repeated, first factor the concentration of auxin growth regulator (without treatment, 100 ppm, 200 ppm and 300 ppm), the second factor are entres length (5 cm, 10 cm and 15 cm). The data analyzed with “F” test and if the result are different with LSD test.The concentration of auxin growth regulator with regression test and entres lengthwere tested used ortogonal contrast. The result shows that concentration of auxin growth regulator is really significantly different for variables age of shoot growth, increase in shoot length, shoot length, number of shoots, number of branches, number of leaves, rootstock diameter and plant height and were significantly different in the variables of percentage of live connections and age of bud break, for concentration 200 ppm (K2) gives the best result to grows up of avocado plant seeds, the treatment for entres lengthare really significantly different to variable age of bud break, age of shoot growth, increase in shoot length, shoot length, number of branches, rootstock diameter and plant height and significantly different on the variable number of shoots. The interaction of concentration of auxin growth regulator and entres length are really significantly different on the variable length of shoots and significantly different on the variable length of entres and number of branches. The best interaction is the duration of concentration of auxin growth regulator and entres length for concentration200 ppm with 15 cmlength (K2P3).